2020
DOI: 10.3390/ijerph17197022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anthropometric Parameters and Throwing Speed in Amateur Male Handball Players at Different Ages

Abstract: The objectives of this study were: (i) to analyse anthropometric parameters and throwing speed from seven meters in amateur male handball players of different ages; (ii) to know the relationship between anthropometric parameters and throwing. One hundred seventy-six male handball players (16.5 ± 5.1 years old) participated in the study, classified according to their age: senior (n = 35), U18 (n = 30), U16 (n = 37), U14 (n = 50) and U12 (n = 24). All participants were evaluated by anthropometric measurements (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
10
0
3
Order By: Relevance
“…The second function that explains only about 12% of the total discriminative power is determined by body height. This result is supported by previous studies that found a decreasing effect of body height on throwing speed with age [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…The second function that explains only about 12% of the total discriminative power is determined by body height. This result is supported by previous studies that found a decreasing effect of body height on throwing speed with age [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this line, recent research shows that a shorter throwing distance predetermines the effectiveness [2,7,11]. In addition, anthropometric characteristics, throwing velocity [12] and technical-tactical skills are also important for successful participation in elite-level handball [13]. In addition, various articles used the throwing variables as discriminant elements between the winning and losing teams [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This analysis, in addition to being novel for junior players, is important because it allows coaches, if necessary, to reduce the number of tests to be applied or to prioritize the result of some tests over others when establishing a test battery. Especially in junior players, as in this case, that although they are still in a training process, their level of biological maturation is high and therefore anthropometric factors will not undergo major changes or be affected by age and maturity as happens in other lower categories [41,42].…”
Section: Discussionmentioning
confidence: 96%